Upaya guru dalam meningkatkan semangat belajar siswa untuk memahami sejarah uang di MI Tarbiyatul Banin Banat Tuban - Andika, Moch. Farizal Fitri (Maliki Interdisciplinary Journal, 2024)
This research aims to analyze the efforts of teachers in enhancing students' motivation and enthusiasm for learning the history of money in the fourth grade at MI Tarbiyatul Banin Banat Tuban. The learning process involves qualitative methods, including interviews and observations. This study found that the lack of student motivation to learn is not solely due to low ability but also due to a lack of enthusiasm. One strategy used to address this issue is the demonstration teaching method, where students actively engage in practicing concepts such as bartering and the use of precious metals as transaction tools. Additionally, the utilization of technology through the use of educational videos and the Quizizz platform, as well as a contextual approach that relates the material to everyday life, was also implemented. The results of the study show that these varied and innovative teaching methods significantly increase students' motivation and understanding of the history of money. This effort can serve as a model for other educational institutions facing similar challenges and provide insights for educators in developing effective teaching methods.